Grade III meningioma: 10 year single centre case series. (12th October 2019) - Mcgrath, Hari; Lavrador, Jose; Christodoulides, Ioannis; Ghimire, Prajwal; Gullan, Richard; Bhangoo, Ranjeev; Ashkan, Keyoumars; Vergani, Francesco
Abstract: Rationale: WHO Grade 3 meningiomas are a rare, malignant subtype of meningioma. Few controlled case series detailing its treatment and follow-up are to be found in the literature. Methods: Retrospective cohort study of patients treated in a single neuro-oncology centre in the period between September 2008 and March 2019 with an initial diagnosis of WHO Grade 3 meningioma. Demographic and clinical data has been collected from the available medical records. Results: 9 patients were included in this series: 2 had convexity, 2 sphenoid wing, 2 parafalcine, 1 parasagittal with a further 3 multiple locations and 1 patient with parietal convexity meningioma. 3 tumours displayed rhabdoid features, whilst 4 displayed papillary features and a further 2 displayed epithelial structures. All patients underwent surgical intervention: 5 patients had a subtotal resection with 3 having total resection. 3/4 of reported Simpson Grading was grade 2, whilst the remaining 1/4 was grade 1. The extent of resection for 1 patient was uncertain. Post surgically, 6 received adjuvant radiotherapy, 2 had no further treatment and 1 received gamma knife therapy. No patient received chemotherapy. 5 patients saw no tumour recurrence at follow up appointments (mean 50 months). Within 2 years of their respective surgical interventions, 4 patients died due to tumour recurrence and associated complications (3 patients). Conclusion: To establish a uniform approach to treatment of patients with WHO Grade 3 meningiomas is challenging. Management involves a patient-centred approach based on multidisciplinary meeting decisions. Multicentre registries may allow further conclusions.